Evaluation of antioxidant and anti-tyrosinase activities of surfactant and alcohol extracted Combretum Indicum leaves - Thanaseelan, Tanesha; D. Nurul, Hidayu; Nurul, Sahirah; Rajaletchumy, Veloo Kutty (Elsevier Ltd, 2024)
Combretum Indicum (CI), which contains numerous bioactive compounds, has been used in traditional medicine for a variety of reasons, including the treatment of skin conditions. This study investigates the antioxidant and anti-tyrosinase activities of CI leaves extracted using different surfactants (Triton X-100 and Vitamin E TPGS) at concentrations of 1%, 2%, and 3%, as well as various alcohol solvents (acetone, methanol, and ethanol) at concentrations of 50%, 70%, and 90%. The antioxidant activity of the extracts has been evaluated using Total Phenolic Content (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH), while the anti-tyrosinase activity was assessed through a mushroom tyrosinase inhibition assay. Prior to analysis, CI leaves had been macerated, extracted, and freeze-dried. The research established that ethanol at a concentration of 50% is the optimum solvent to extract CI leaves, as it demonstrated good antioxidant and anti-tyrosinase action with a high percentage of yield and total phenolic content. As a result, the outcomes of this study contribute to a better understanding of the potential applications of CI leaf extract in cosmetics, notably in the treatment of oxidative stress and hyperpigmentation. Further study and development in this field could lead to the creation of effective and natural cosmetic products produced from CI leaves that have antioxidant and anti-tyrosinase effects.